2020
DOI: 10.1080/13102818.2020.1734085
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications associated with multilevel anterior cervical decompression and fusion technique in a large prospective study

Abstract: This study describes our experience with the treatment of cervical degenerative pathology through anterior cervical decompression and fusion technique. We evaluated the clinical outcome and complications after 6-months follow-up and analysed the data to optimize the efficacy and safety of this particular surgical treatment in order to minimize the risks of complications. The presented study included 111 patients (74 men and 37 women; mean age 56.5 years) treated in the Neurosurgical Department of UMBAL Sv. Iva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The dural tear is one of the relatively few complications, as it occurred in the current study at a rate of 0.9% in a patient who underwent ACCF surgery. Mihaylova et al (2020) reported a dural tear rate of 2.7%, all of which occurred in patients who underwent ACCF surgery. Thickening or calcification of PLL significantly increases the risk of dural tear.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The dural tear is one of the relatively few complications, as it occurred in the current study at a rate of 0.9% in a patient who underwent ACCF surgery. Mihaylova et al (2020) reported a dural tear rate of 2.7%, all of which occurred in patients who underwent ACCF surgery. Thickening or calcification of PLL significantly increases the risk of dural tear.…”
Section: Risk Factorsmentioning
confidence: 99%